Oxidative stress‐induced structural changes in the microtubule‐associated flavoenzyme Irc15p from Saccharomyces cerevisiae. (17th December 2018) - Koch, Karin; Strandback, Emilia; Jha, Shalinee; Richter, Gesa; Bourgeois, Benjamin; Madl, Tobias; Macheroux, Peter
Abstract: The genome of the yeast Saccharomyces cerevisiae encodes a canonical lipoamide dehydrogenase (Lpd1p) as part of the pyruvate dehydrogenase complex and a highly similar protein termed Irc15p (increased recombination centers 15). In contrast to Lpd1p, Irc15p lacks a pair of redox active cysteine residues required for the reduction of lipoamide and thus it is very unlikely that Irc15p performs a similar dithiol‐disulfide exchange reaction as reported for lipoamide dehydrogenases. We expressed IRC15 in Escherichia coli and purified the produced protein to conduct a detailed biochemical characterization. Here, we show that Irc15p is a dimeric protein with one FAD per protomer. Photoreduction of the protein generates the fully reduced hydroquinone without the occurrence of a flavin semiquinone radical. Similarly, reduction with NADH or NADPH yields the flavin hydroquinone without the occurrence of intermediates as observed for lipoamide dehydrogenase. The redox potential of Irc15p was −313 ± 1 mV and is thus similar to lipoamide dehydrogenase. Reduced Irc15p is oxidized by several artificial electron acceptors such as potassium ferricyanide, 2, 6‐dichlorophenol‐indophenol, 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2 H ‐tetrazolium bromide, and menadione. However, disulfides such as cystine, glutathione, and lipoamide were unable to react with reduced Irc15p. Limited proteolysis and SAXS‐measurements revealed that the NADH‐dependent formation of hydrogen peroxide caused a substantial structural change in the dimeric protein. Therefore, we hypothesize that Irc15p undergoes a conformational change in the presence of elevated levels of hydrogen peroxide, which is a putative biomarker of oxidative stress. This conformational change may in turn modulate the interaction of Irc15p with other key players involved in regulating microtubule dynamics.